Pengaruh Word Of Mouth, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Tenun Ikat Kodok Ngorek Di Kota Kediri Tahun 2025 - Machsun Machsun; Abdul Halik; Siti Mujanah (STIE AUB Surakarta, 2025)
This study aims to analyze the influence of word of mouth, product quality and price on purchasing decisions for Kodok Ngorekikat weaving in Kediri City.This research is an analytical observational study with a cross-sectional approach. The sampling technique used was simple random sampling. The population was all consumers of Kodok Ngorek ikat weaving in Kediri City. The sample size was 103 respondents. The independent variables were word of mouth, product quality, and price. The dependent variable was the purchasing decision. Statistical analysis used logistic regression.The results of the analysis show that word of mouth (0.005), product quality (0.001) and price (0.003) influence the purchasingdecision to Tenun Ikat Kodok Ngorek.